2021
DOI: 10.3389/fcell.2020.637435
|View full text |Cite
|
Sign up to set email alerts
|

Role of Non-coding RNAs on the Radiotherapy Sensitivity and Resistance of Head and Neck Cancer: From Basic Research to Clinical Application

Abstract: Head and neck cancers (HNCs) rank as the sixth common and the seventh leading cause of cancer-related death worldwide, with an estimated incidence of 600,000 cases and 40–50% mortality rate every year. Radiotherapy is a common local therapeutic modality for HNC mainly through the function of ionizing radiation, with approximately 60% of patients treated with radiotherapy or chemoradiotherapy. Although radiotherapy is more advanced and widely used in clinical practice, the 5-year overall survival rates of local… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 113 publications
0
5
0
Order By: Relevance
“…Recently, lncRNAs have gained increasing attention in targeted therapy of human cancer ( 38 40 ). At present, targeting lncRNAs can be achieved through multiple different approaches, such as transcription block, degradation and gene-editing technology ( 41 , 42 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, lncRNAs have gained increasing attention in targeted therapy of human cancer ( 38 40 ). At present, targeting lncRNAs can be achieved through multiple different approaches, such as transcription block, degradation and gene-editing technology ( 41 , 42 ).…”
Section: Discussionmentioning
confidence: 99%
“…ncRNAs, a special class of RNA transcripts, do not encode proteins but exhibit high specificity and stability, making them crucial for assessing the occurrence and progression of cancer [ 23 , 24 ]. Based on their functions, ncRNAs are typically categorized into housekeeping RNAs and regulatory RNAs [ 25 ]. Regulatory RNAs mainly include miRNAs, lncRNAs, and circRNAs [ 23 , 24 , 25 , 26 ].…”
Section: Introduction To the Wnt Signaling Pathway And The Involvemen...mentioning
confidence: 99%
“…Based on their functions, ncRNAs are typically categorized into housekeeping RNAs and regulatory RNAs [ 25 ]. Regulatory RNAs mainly include miRNAs, lncRNAs, and circRNAs [ 23 , 24 , 25 , 26 ]. miRNAs are extensively studied small non-coding RNAs (sncRNAs) in eukaryotes and consist of approximately 22 nucleotides (nt) in length [ 27 ].…”
Section: Introduction To the Wnt Signaling Pathway And The Involvemen...mentioning
confidence: 99%
“…Worldwide, the deep anatomic localization of NPC and its late diagnosis limit therapeutic approaches, and radiotherapy is still the main and the most effective treatment of NPC [3]. Scientific evidence has shown that radiotherapy destroys tumour cells by acting directly on the DNA (direct effect), and indirectly by free radicals generated by ionization leading to DNA base lesion (indirect effect) [4]. This DNA injury eventually impacts cell proliferation and changes the cell cycle, inducing cellular apoptosis or activating death pathways [5].…”
Section: Introductionmentioning
confidence: 99%